Quasi Score is more efficient than Corrected Score in a polynomial measurement error model - Sergiy Shklyar; Hans Schneeweiss; Alexander Kukush (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2005)
We consider a polynomial regression model, where the covariate is measured with Gaussian errors. The measurement error variance is supposed to be known. The covariate is normally distributed with known mean and variance. Quasi Score (QS) and Corrected Score (CS) are two consistent estimation methods, where the first makes use of the distribution of the covariate (structural method), while the latter does not (functional method). It may therefore be surmised that the former method is (asymptotically) more efficient than the latter one. This can, indeed, be proved for the regression parameters. We do this by introducing a third, so-called Simple Score (SS),estimator, the efficiency of which turns out to be intermediate between QS and CS. When one includes structural and functional estimators for the variance in the equation, SS is still more efficient than CS. When the mean and variance of the covariate are not known and have to be estimated as well, one can still maintain that QS is more efficient than SS for the regression parameters.
urn:nbn:de:bvb:19-epub-1814-6
Keywords: 519; Quasi Score; Corrected Score; Polynomial Model; Measurement Errors; Efficiency; Structural Methods; Functional Methods